The road to molecular identification and detection of fungal grapevine trunk diseases - Azevedo-Nogueira, Filipe (2022)
Grapevine is regarded as a highly profitable culture, being well spread worldwide and mostly directed to the wine-producing industry. Practices to maintain the vineyard in healthy conditions are tenuous and are exacerbated due to abiotic and biotic stresses, where fungal grapevine trunk diseases (GTDs) play a major role. The abolishment of chemical treatments and the intensification of several management practices led to an uprise in GTD outbreaks. Symptomatology of GTDs is very similar among diseases, leading to underdevelopment of the vines and death in extreme scenarios. Disease progression is widely affected by biotic and abiotic factors, and the prevalence of the pathogens varies with country and region. In this review, the state-of-the-art regarding identification and detection of GTDs is vastly analyzed. Methods and protocols used for the identification of GTDs, which are currently rather limited, are highlighted. The main conclusion is the utter need for the development of new technologies to easily and precisely detect the presence of the pathogens related to GTDs, allowing to readily take phytosanitary measures and/or proceed to plant removal in order to establish better vineyard management practices. Moreover, new practices and methods of detection, identification, and quantification of infectious material would allow imposing greater control on nurseries and plant exportation, limiting the movement of infected vines and thus avoiding the propagation of fungal inoculum throughout wine regions